Work-Life Balance, Job Satisfaction, and Career Development of Millennials: The Mediating Role of Affective Commitment - Tyna Yunita; Hadita Hadita; Murti Wijayanti; Vivi Ismayani (Universitas Hayam Wuruk Perbanas, 2023)
Since millennials dominate today’s workforce, it is necessary to explore the career development of this generation. Therefore, this study aims to examine the career development of the millennial generation based on work-life balance and satisfaction factors mediated by affective commitment. This study involved 160 respondents, most of whom were female manufacturing workers. This study took a quantitative approach and used structural equation modeling to examine predictors of career development among millennials. We found that work-life balance and job satisfaction positively affect affective commitment and affective commitment positively affects career development. However, the results revealed no direct relationship between work-life balance and career development. The effect of work-life balance on career development is only significant if it is mediated by job satisfaction. A clear and targeted career path is very important for the continuity of millennial career development. This study suggests technology-based ways to engage millennials using digital tools to interact and share information, resulting in better work-life balance and higher productivity. This study implies that work-life balance is necessary for enhancing job satisfaction, emotional commitment, and career advancement.